2007
DOI: 10.1111/j.1469-7580.2007.00804.x
|View full text |Cite
|
Sign up to set email alerts
|

Fractal dimension as a quantitator of the microvasculature of normal and adenomatous pituitary tissue

Abstract: It is well known that angiogenesis is a complex process that accompanies neoplastic growth, but pituitary tumours are less vascularized than normal pituitary glands. Several analytical methods aimed at quantifying the vascular system in two-dimensional histological sections have been proposed, with very discordant results. In this study we investigated the non-Euclidean geometrical complexity of the two-dimensional microvasculature of normal pituitary glands and pituitary adenomas by quantifying the surface fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…Furthermore, studies of hepatocelluar carcinomas have shown an increase in the fractal dimension of vasculature structures in malignant tissue compared to normal tissue, where the vessels of primary tumors showed greater fractal dimension when compared with hepatic metastases [55]. Conversely, fractal studies have also demonstrated that the microvasculature in normal pituitary tissue is more complex than in benign pituitary adenomas [56] and correlates with earlier findings demonstrating reduced microvascular complexity in malignant PRL producing carcinomas vs. benign pituitary adenomas [57]. Hence, it may be that some pituitary tumors may progress via a non-angiogenic pathway, which has also been demonstrated in a subclass of primary non-small cell lung cancers and glioblastomas which progress without neo-vascularisation and are more clinically aggressive than angiogenic tumors [58][59][60][61].…”
Section: Cancermentioning
confidence: 99%
“…Furthermore, studies of hepatocelluar carcinomas have shown an increase in the fractal dimension of vasculature structures in malignant tissue compared to normal tissue, where the vessels of primary tumors showed greater fractal dimension when compared with hepatic metastases [55]. Conversely, fractal studies have also demonstrated that the microvasculature in normal pituitary tissue is more complex than in benign pituitary adenomas [56] and correlates with earlier findings demonstrating reduced microvascular complexity in malignant PRL producing carcinomas vs. benign pituitary adenomas [57]. Hence, it may be that some pituitary tumors may progress via a non-angiogenic pathway, which has also been demonstrated in a subclass of primary non-small cell lung cancers and glioblastomas which progress without neo-vascularisation and are more clinically aggressive than angiogenic tumors [58][59][60][61].…”
Section: Cancermentioning
confidence: 99%
“…It has been shown that angiogenesis is a hallmark of the progression of medulloblastoma and, over the last years, investigators have sought to develop effective and less toxic antiangiogenic strategies, including the inhibition or destruction of abnormal blood vessels using either antiangiogenic or vascular disrupting agents. However, the results are conflicting, principally because of the complex biology of tumor vasculature and the irregular geometry of the vascular system in real space (55)(56)(57)(58). In addition, current targets of antiangiogenic therapy, such as VEGF, are thought to be critical for both physiologic and pathologic angiogenesis, and clinical side effects of anti-VEGF therapy are beginning to emerge (59).…”
Section: Antiangiogenesis In Medulloblastoma: Is It a Helpful Approach?mentioning
confidence: 99%
“…Currently, there are no markers of the net angiogenic activity of a tumor that can help investigators to design specific antiangiogenic treatment strategies (42,65), but it is reasonable to resume that the quantification of various aspects of tumor vasculature may provide an indication of angiogenic activity (55)(56)(57)(58).…”
Section: Antiangiogenesis In Medulloblastoma: Is It a Helpful Approach?mentioning
confidence: 99%
See 2 more Smart Citations